ChemInform Abstract: Synthesis of 1H‐1, 2, 3‐Triazole Linked β‐Lactam—Isatin Bi‐Functional Hybrids and Preliminary Analysis of in vitro Activity Against the Protozoal Parasite Trichomonas vaginalis. Issue 41 (19th September 2013) - Raj, Raghu; Singh, Pardeep; Haberkern, Nathan T.; Faucher, Ryan M.; Patel, Neal; Land, Kirkwood M.; Kumar, Vipan
Abstract The compound (I) exhibits in vitro 100% growth inhibition at 100 μM against T.